Cryopiece, a novel carrier with faster cooling rate, high recovery rate and retrieval rate, for individual sperm cryopreservation - Zhu, Zi-Jue; Zhai, Jing; Hu, Jian-Lin; Wang, Yi-Zhou; Chen, Wei; Liu, Feng; Huang, Yong-Hua; Li, Zheng (Translational andrology and urology, 2021)
Cryopreservation of extremely few spermatozoa is still a major challenge for male fertility preservation. This study aims to evaluate the cooling rate, recovery rate, and retrieval rate, along with other parameters of spermatozoa that cryopreserved using Cryopiece, a novel carrier, for individual sperm cryopreservation. Semen samples from 60 fertile donors were collected, and each semen sample was screened for motile sperm and mixed with cryoprotective agent (CPA), and then frozen using Cryopiece, micro-straw, and mini-straws. The cooling rate, retrieval rate, and recovery rate, morphology, DNA fragmentation index (DFI) and mitochondrial membrane potential (MMP), were compared among the un-frozen sperm and the sperm cryopreserved using these carriers. Cryopiece possessed the fastest cooling rate. After freeze-thaw, the average retrieval rate of sperm cryopreserved using Cryopiece was 96.25%, and the average recovery rate was 64.40%, which were higher than that of sperm cryopreserved using the other two carriers (71.42% and 54.30% for micro-straw, and 63.54% and 58.04% for mini-straw, respectively). There was no significant impact on DFI after sperm cryopreservation, and no significant difference in morphology between sperm cryopreserved using these carriers was observed. Though MMP of sperm changed significantly after cryopreservation, micro-straw maintained sperm MMP better than Cryopiece and mini-straw did, while no significant difference was observed in MMP between sperm cryopreserved using Cryopiece and mini-straw. Cryopiece produced satisfying retrieval and recovery rates in sperm cryopreservation and should be an ideal carrier for cryopreservation of small number of sperm.